Associations Between Smartphone Use for Physical Activity by South Korean College Students and Behavioral Change Constructs of the Transtheoretical Model. Issue 4 (August 2022) - Kim, Byoung-hoon; Lee, Hyo
We examined associations between smartphone uses to assist physical activity (PA) and change constructs of the transtheoretical model (TTM) among Korean college students. Our participants were 242 college students who completed a cross-sectional survey of their smartphone use, PA, and TTM constructs. We applied Poisson regression models to test the associations between stages of change and smartphone PA use frequencies in four categories over the previous week: 1= watching PA instruction videos; 2 = tracking PA; 3 = searching and booking sites for PA; and 4 = finding and making appointments with PA partners. The associations between these smartphone uses and participants' self-efficacy, decisional balance, processes of change, and PA were tested via ordinary least squares regression models. Results were that participants in the precontemplation and maintenance stages were the least and most frequent users of the smartphones in all four categories, respectively. Category one usage was positively associated with participants' scores on pros (β = .22, p = .004), cognitive processes of change (β = .30, p < .001), and behavioral processes of change (β = .28, p < .001). Category two usage was positively associated with PA (β = .06, p = .048). While category three usage was not significantly associated with any TTM constructs except for stages of change, category four usage was positively associated with self-efficacy (β = .28, p < .001), pros (β = .30, p < .001), cognitive processes of change (β = .31, p < .001), behavioral processes of change (β = .06, p <. 001), and PA (β = .45, p < .001). These findings suggest that (a) active college students are likely to take advantage of smartphone to assist their PA, and (b) smartphones can help motivate college students toward regular PA.